Study of rituximab cost and its off-label-use. Issue 2 (12th March 2012) - Martínez, S.; Esteban, M.; Alfaro, M.A.; Merchante, M.; Barajas, M.T.; Zorzano, A.P.; Aibar, M.P.; Izquierdo, A.
Abstract : Background: Rituximab is used in Non-Hodgkin Lymphoma (NHL), Chronic Lymphocytic Leukaemia (CLL) and Rheumatoid Arthritis (RA). Moreover, it has other uses which are not included in Technical Data Sheet (TDS). Purpose: To analyse the off-label-use of Rituximab and estimate the global cost of Rituximab treatment. Materials and methods: Retrospective and descriptive study, in which all patients who received Rituximab between January and June, 2011, are included. The list of patients, dose and number of cycles administered were extracted from the Oncogest ® program. From the electronic medical record ( Selene x00AE; Siemens 5.1.0.1) the following were obtained: sex, age, diagnosis and prescribing services. The total cost was estimated by summing the sale price corresponding to the total dose for each patient. Results: Number of patients: 79; Male: 54.4%; Female: 45.6%; Average age: 61.3 years (range: 16-87). In 67 patients (84.8%) the diagnosis were described in TDS: NHL 46 (52.8%), CLL 19 (24.1%) and RA 2 (2.5%). In 12 patients (15.2%) the indication was not included in TDS, among these the most frequent use was Idiopathic Thrombocytopenic Purpura (ITP) (4 patients). The departments which most frequently prescribed Rituximab were: Haematology (78.5%) and Oncology (11.4%). The average dose per chemotherapy cycle was 697 mg and the average number of cycles per patient was 3.1. The total cost of Rituximab was €408 370 and the average cost per patient was €5 169. The cost of approved treatments responded for 84% of the total cost (€342 889). Conclusions: Rituximab was mostly used in label conditions, mainly in NHL treatment. Label use was associated with the highest cost of Rituximab. Moreover, the average cost per patient with CLL proved to be higher than all other approved uses, because the total doses administered, as well as the number of cycles, were higher. The most common diagnosis off-label-use was ITP.